MORPHOLOGICAL STATE EXTRAORGANIC BLOODSTREAM PINEAL GLAND OF RATS IN ACUTE IMMOBILIZATION STRESS, AND PERMANENT LIGHTING - Pshychenko, V.V.; Volobuev, N.A. (World of Medicine and Biology, 2013)
Conducted a study on the characteristics of extraorganic bloodstream pineal gland in rats and morphological manifestations of the rheological properties of blood after a 5-hour immobilization stress and normal function of the pineal gland. Found that the blood vessels of the venous blood type violations occur due to adhesion of red blood cells, blood separation, necrosis and lysis of red blood cells, as well as violation of the integrity of the vascular wall. Found that morphological data breach involving suppression of functional activity of the pineal gland.